2020
DOI: 10.5858/arpa.2020-0186-sa
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19–Associated Hepatitis Complicating Recent Living Donor Liver Transplantation

Abstract: We present a case of COVID-19 hepatitis in a living donor liver allograft recipient whose donor subsequently tested positive for COVID-19. The patient is a female infant with biliary atresia (failed Kasai procedure). She recovered well, with improving liver function tests for 4 days. On post-operative day (POD) 4 the patient developed respiratory distress and fever. COVID-19 testing (polymerase chain reaction) was positive. Liver function tests increased approximately 5fold. Liver biopsy showed moderate acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
1
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 9 publications
2
76
1
5
Order By: Relevance
“…The characteristics of included trials were presented in Table 1 . A total of 269 patients from 47 studies [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] were included in our meta-analysis. The mean age of operative patients with COVID-19 was 50.91 [95% CI, 42.49; 59.34], and 49% [95% CI, 0.33, 0.65] patients were female.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of included trials were presented in Table 1 . A total of 269 patients from 47 studies [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] were included in our meta-analysis. The mean age of operative patients with COVID-19 was 50.91 [95% CI, 42.49; 59.34], and 49% [95% CI, 0.33, 0.65] patients were female.…”
Section: Resultsmentioning
confidence: 99%
“…Seven did not require hospitalization, and mortality affected 21% of the patients. There are 3 recent cases reported from the United States, [10][11][12] with good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…There is a report of a LT recipient with perioperative infection, 3 two cases during follow-up in China, 4,5 3 cases from Lombardy, 6 6 cases from Madrid, 7 9 from an International Registry, 8 24 from a survey in Italy, 9 and 3 more in the United States. [10][11][12] Therefore, we aimed at presenting our preliminary experience involving COVID-19 in the LT population during the first 2 months of this pandemic crisis in Madrid.…”
mentioning
confidence: 99%
“…There is still limited knowledge about the course of in liver transplant recipients, especially in the case of early post-LT infection. 4,5 Recent series from USA 6 and Spain 7 have suggested that recipients of solid organ transplant affected by COVID-19 may present higher mortality as compared to the general population.…”
Section: Introductionmentioning
confidence: 99%